The Correlation between Knowledge Level and Cariogenic Animated Video Playback in 10 to 12-year-old Children - Nyka Dwi Febria; Bellariani Khairunnisa (Universitas Muhammadiyah Yogyakarta, 2022)
Recently, technology has developed massively. The utilization of technology has benefited all aspects of human life. One field has benefitted from technology as a tool for innovation in education. Health education, including dental and oral health, makes the use of audio-visual media as an impact of technology development for teaching tools. The teaching tool is used for children of the school-age (10-12 years old) by utilizing videos that describe cariogenic food. It is conducted since children are likely to consume food causing dental caries. This study aims to identify animated video effects on knowledge enhancement about cariogenic food in children of 10-12 years old. This study is quasi-experimental with a pre-test and post-test design. The study sample included 32 students of 10-12 years old. The students filled out the pre-test sheet, watched animated videos, and completed an online post-test sheet. Data analysis was carried out using the statistical test of the Wilcoxon signed-rank test. The mean pre-test score was 79.17, while the post-test was 82.03. The difference between pre and post-test was 2.86. A normality test of data distribution was conducted using the Shapiro Wilk test and showed that the data distribution was not normal. Wilcoxon test results showed a significance value of 0.274 (p0.05). As a result, an animated video showed no significant increase in knowledge level about cariogenic food in children of 10-12 years old.